Retrospective casuistry report from a wild and exotic animal clinic in Paraguay - Vetter Hiebert, Joerg Richard (2025)
The aim of this study was to present retrospective data on species treated at the Wild and Exotic Animal Clinic of the National University of Asunción, Paraguay, between 2015 and 2022. Data were collected from all medical records to classify the species that attended the Clinic. A total of 2565 patients were attended, with mammals accounting for 48.54%, birds 38.64%, and reptiles 12.82%. The most common mammal recorded at the clinic was the domestic rabbit (Oryctolagus cuniculus), the most common bird was the blue-fronted amazon (Amazona aestiva), and the most common reptile was the Chaco tortoise (Chelonoidis chilensis), representing 20.6, 14.5, and 5.8%, respectively, of the total number of patients registered during the study period. The results presented are the first report seeking to estimate and quantify the domestic ownership of wild and exotic animals in Paraguay, and the impact of illegal wildlife trafficking.